2004
DOI: 10.1099/mic.0.27421-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Bacillus subtilis  B regulators in cell extracts

Abstract: The general stress regulon of Bacillus subtilis is induced by the activation of the s B transcription factor. Activation of s B occurs as a consequence of the dephosphorylation of its positive regulator RsbV by one of two phosphatases that respond to either physical or nutritional stress. The physical stress phosphatase (RsbU) requires a second protein (RsbT) for activity. Stress is thought to initiate a process that triggers the release of RsbT from a large inhibitory complex composed of multiple copies of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
(44 reference statements)
0
19
1
Order By: Relevance
“…Gel filtration analysis. Gel filtration was performed as previously described (25). One-liter Escherichia coli cultures expressing the desired rsb alleles were grown to a mid-logarithmic stage (optical density at 540 nm [OD 540 ], 0.5), quickly chilled by the addition of ice, and harvested by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Gel filtration analysis. Gel filtration was performed as previously described (25). One-liter Escherichia coli cultures expressing the desired rsb alleles were grown to a mid-logarithmic stage (optical density at 540 nm [OD 540 ], 0.5), quickly chilled by the addition of ice, and harvested by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…B activity is regulated by eight proteins encoded in the sigB operon through protein-protein interactions in B. subtilis (15,30). Similarly, B activation has also been observed to increase cell survival in B. cereus under the above-described conditions (45).…”
mentioning
confidence: 99%
“…In recent work, we found that the large RsbR complexes present in crude bacterial extracts include RsbS but not RsbT (21). Although not part of the RsbR complexes, RsbT was also in a high-molecular-weight form that was Triton X-100 sensitive and likely an RsbT aggregate.…”
mentioning
confidence: 99%
“…In unstressed B. subtilis, RsbT is thought to be bound to an inhibitory protein (RsbS) in a high-molecular-mass complex (Ͼ10 6 Da) formed by members of a family of homologous proteins (RsbRA, -RB, -RC, and -RD) (10,20,21). The RsbR complex appears to modulate the interactions between RsbS and RsbT (1,2,10,14).…”
mentioning
confidence: 99%